Analysis of Brand Equity in Enhancing Repeat Visitation Rates in the Hospitality Industry - Lorenza, Sara; Octafian, Ray (Jurnal Mantik, 2024)
The hospitality industry is a highly competitive industry, where each hotel competes to attract customers and increase repeat visitation rates. One important factor that can help hotels achieve these goals is brand equity. This research aims to explore the role of brand equity in increasing repeat visitation rates in the hospitality industry. The study uses a qualitative approach with in-depth interviews and a case study at HARRIS Hotel Sentraland Semarang. The research concludes that brand equity plays a crucial role in increasing repeat visitation rates in the hospitality industry. By building strong brand equity through strategies focusing on brand awareness, brand associations, perceived quality, and brand loyalty, hotels can enhance their appeal to customers and encourage them to return for future stays